Thionitroxyl Radical (H2NS) Isomers: Structures, Vibrational Spectroscopy, Electronic States and Photochemistry - Jarraya, Mahmoud; Ben Yaghlane, Saida; Feifel, Raimund; Linguerri, Roberto; Hochlaf, Majdi (Frontiers in Astronomy and Space Sciences, 2021)
The thionitroxyl radical (H2NS) isomers are characterized using advanced ab initio methodologies. Computations are done using standard and explicitly correlated coupled cluster, CASSCF and MRCI approaches in conjunction with large basis sets, extrapolated to the complete basis set (CBS) limit. The lowest electronic states of different isomers are mapped along the stretching coordinates, thereby confirming the existence of the four already known ground state structures, namely H2NS, H2SN, cis-HNSH and trans-HNSH. Also, it is shown that only the lowest electronic excited states are stable, whereas the upper electronic states may undergo unimolecular decomposition processes forming H + HNS/HSN or the HN + SH or N + H2S or S + NH2 fragments. These data allow an assignment of the deep blue glow observed after reactions between “active nitrogen” and H2S at the beginning of the XXth century. For stable species, a set of accurate structural and spectroscopic parameters are provided. Since small nitrogen-sulfur molecular species are of astrophysical relevance, this work may help for identifying the thionitroxyl radical isomers in astrophysical media and in the laboratory.